Network spreading and local biological vulnerability in amyotrophic lateral sclerosis - Asa Farahani; Justine Y. Hansen; Vincent Bazinet; Golia Shafiei; D. Louis Collins; Mahsa Dadar; Sanjay Kalra; Alain Dagher; Bratislav Misic (Communications Biology)
Abstract Amyotrophic Lateral Sclerosis (ALS) is a progressive neurodegenerative disease that predominantly targets the motor system. Spread of pathology is thought to be driven by both local vulnerability and network architecture. Namely, molecular and cellular features may confer vulnerability to specific neuronal populations, while synaptic contacts may also increase exposure to pathology in connected neuronal populations. However, these principles are typically studied in isolation and it remains unknown how local vulnerability and network spreading interact to shape cortical atrophy. Here, we investigate how network structure and local biological features shape the spatial patterning of atrophy in ALS. We analyze the Canadian ALS Neuroimaging Consortium (CALSNIC) dataset and estimate cortical atrophy using deformation based morphometry (DBM). The course of atrophy closely aligns with structural connectivity. Atrophy is also more likely to occur in regions that share similar metabolic profiles. Disease epicenters are located in motor cortex. Epicenter probability maps show transcriptomic enrichment for biological processes involved in mitochondrial function as well as support cells, including endothelial cells and pericytes. Finally, individual differences in epicenter location correspond to individual differences in clinical and cognitive symptoms and differentiate patient subtypes.